2021
DOI: 10.1177/03000605211015018
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early postoperative hypocalcemia in patients with secondary hyperparathyroidism undergoing total parathyroidectomy

Abstract: Objective To summarize the clinical features of secondary hyperparathyroidism (SHPT) in patients with chronic renal failure and to explore the predictive factors of postoperative hypocalcemia after total parathyroidectomy in these patients. Methods The clinical data of 87 patients admitted to Guangdong Electric Power Hospital from May 2013 to February 2020 were reviewed. All patients underwent total parathyroid resection and sternocleidomastoid microtransplantation. Age, sex, and the serum calcium, phosphorus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
3
9
0
Order By: Relevance
“…Consistent with the present findings, it has previously been shown that patients with high preoperative ALP activities are at higher risk of postoperative hypocalcemia ( 31 , 32 ). A study by Yang et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the present findings, it has previously been shown that patients with high preoperative ALP activities are at higher risk of postoperative hypocalcemia ( 31 , 32 ). A study by Yang et al.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the present findings, it has previously been shown that patients with high preoperative ALP activities are at higher risk of postoperative hypocalcemia (31,32). A study by Yang et al (33) also showed that patients with preoperative serum ALP activities > 277 U/L are susceptible to postoperative hypocalcemia, but the clinical utility of ALP alone for the prediction of hypocalcemia was unsatisfactory in this study, whereas the combined index identified in the present study is a more accurate predictor.…”
Section: Discussionsupporting
confidence: 84%
“…In total, five studies mentioned the results of age [ 5 , 14 , 15 , 18 , 19 ]. The statistical heterogeneity was high (I 2 =82%, p = 0.0002), and a random-effects model was used to perform a meta-analysis was performed on the unadjusted data.…”
Section: Resultsmentioning
confidence: 99%
“…In total, six studies (including seven groups of data) reported the results of preoperative iPTH 2 [ 14 , 16 , 17 , 19 , 21 ],. Due to the high statistical heterogeneity (I 2 =94%) ( p < 0.00001), a random-effects model was utilized for the meta-analysis of the unadjusted data.…”
Section: Resultsmentioning
confidence: 99%
“…The major criticism is the lack of a clear PTH threshold for both calcium and vitamin D supplementation. Some authors suggest that PTH may not be the only determinant for the development of hypocalcemia and that other factors may play a major role such as vitamin D deficiency [40], dietary habits [41], and other metabolic disorders such as hypomagnesemia [42,43]. Hypomagnesemia is frequently associated with the use of drugs such as aminoglycosides, cyclosporine, cisplatin, amphotericin B, ACE inhibitors, proton pump inhibitors, and some diuretics (thiazides and loop) [44].…”
Section: Discussionmentioning
confidence: 99%